ความสามารถในการแก้ปัญหาทางคณิตศาสตร์และผลสัมฤทธิ์ทางการเรียน เรื่อง การหาร จากการจัดการเรียนรู้แบบสืบเสาะหาความรู้ 5 ขั้น ของนักเรียนชั้นประถมศึกษาปีที่ 2 โรงเรียนแหลมพันวา จังหวัดภูเก็ต - ลาเต๊ะ ฟาดิ๊ล; จิรวัฒนพาณิช อนุวัตร; ชัยเสนา กันตภน (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were to study the mathematical problem-solving ability and learning achievement through the 5E Inquiry-Based Instructional Model. The target group consisted of 29 Grade 2 students at Laem Panwa School, Phuket, during the 2025 academic year. The research instruments included: 1) the 5E inquiry-based lesson plans, 2) a mathematical problem-solving ability test, and 3) a mathematics learning achievement test. The statistics used for data analysis were mean, standard deviation, and percentage. The research findings were as follows: • The students’ mathematical problem-solving ability after learning through the 5E Instructional Model was at a "Good" level. • The students’ mathematics learning achievement after learning through the 5E Instructional Model was higher, with a post-test mean score of 14.82 a standard deviation of 3.04 which was significantly higher than the 70% threshold.